Technological Transformations in Arabic Language Learning: A Comprehensive Review of Emerging Tools and Techniques - Azmi Islami; Busthomi Ibrohim; Habib Muharrom Sudarmawan; Agung Muttaqien; Faiz Mursyid Lidinillah (Arabiyatuna: Jurnal Bahasa Arab, 2026)
Digital technology has transformed how Arabic is taught and learned worldwide. The scholarly conversation around this shift, however, has grown along parallel but rarely intersecting tracks. Computational researchers concentrate on algorithms, pedagogues refine teaching methods, and sociologists examine cultural contexts, often without engaging one another's findings. This study responds to that problem. It aims to map how technological tools, pedagogical principles, and socio-cultural settings together shape contemporary Arabic language learning, with particular attention to pre-digital traditions such as those maintained in Indonesian Pesantren. The inquiry is urgent because a widening gap exists between the rapid advancement of Arabic learning technologies and the uneven readiness of institutions to adopt them in pedagogically sound and culturally appropriate ways. Two research questions guide the study. (1) What publication trends, geographical distributions, and methodological patterns characterise research on technology-enhanced Arabic language learning from 2020 to 2025? (2) What thematic clusters define this research landscape, and how are they connected? A systematic literature review was conducted under the PRISMA protocol. Scopus served as the primary database, with Google Scholar and Web of Science used for cross-validation. Fifty articles met the inclusion criteria. Two analytical procedures were applied in parallel. A qualitative thematic analysis was organised through the Watase Uake System, a coding framework that maps recurrent concepts into interconnected thematic nodes. A bibliometric analysis then tracked publication trends, journal-tier distribution, and keyword frequency. Results show a paradigm shift from instructor-led teaching toward digitally mediated Arabic learning ecosystems, with research concentrated in the Gulf region and a steadily growing presence from Southeast Asia. Two theoretical anchors dominate the field: Deep Learning for assistive technologies such as Arabic Sign Language recognition, and Self-Determination Theory for questions of learner motivation. Persistent challenges also surface, particularly the digital divide and cultural resistance. Pre-digital pedagogies such as the Muhadatsah method practised in Pesantren continue to shape how technology is received in non-Western contexts.